2023
DOI: 10.3389/fpls.2023.1116006
|View full text |Cite
|
Sign up to set email alerts
|

Novel sources of resistance to fusarium wilt in Luffa species

Abstract: Fusarium wilt is a serious disease of cucurbit crops including cultivated Luffa species (Luffa aegyptiaca, Luffa acutangula) causing considerable amount of reduction in yield and quality. Luffa is starting to be used as rootstocks for major commercial cucurbit crops, but little is known of its resistance against soilborne diseases. Here, 63 Luffa accessions from the World Vegetable Center genebank were evaluated for resistance to an aggressive isolate of Fusarium oxysporum f. FoCu-1 (Fsp-66). According to visu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…It’s essential to emphasize that luffa samples from Malaysia exhibited the highest ratio of plants resistant to Fusarium wilt, while none of the sample from Laos showed resistance. Beyond the potential influence of our sample collection methods and the specific Fusarium species or isolates used for inoculation, which may impact luffa resistance [ 37 ], another plausible explanation for this difference could be the influence of the plants’ geographic origins. The country where luffa plants originated might significantly affect their ability to resist Fusarium wilt due to geographical isolation.…”
Section: Discussionmentioning
confidence: 99%
“…It’s essential to emphasize that luffa samples from Malaysia exhibited the highest ratio of plants resistant to Fusarium wilt, while none of the sample from Laos showed resistance. Beyond the potential influence of our sample collection methods and the specific Fusarium species or isolates used for inoculation, which may impact luffa resistance [ 37 ], another plausible explanation for this difference could be the influence of the plants’ geographic origins. The country where luffa plants originated might significantly affect their ability to resist Fusarium wilt due to geographical isolation.…”
Section: Discussionmentioning
confidence: 99%
“…Hilal et al (2000) tested fungi isolated from the roots and seeds of Luffa aegyptiaca Mill and found that M. phaseolina was not pathogenic to this crop. Subsequent studies also highlighted the resistance of this cucurbitaceous plant when inoculated with other root pathogens (Bruton et al, 2000;Kwon et al, 2001;Namisy et al, 2023;Bindal et al, 2023).…”
Section: Introductionmentioning
confidence: 98%
“…The lack of knowledge about the in uence of diseases transmitted by root pathogens has hindered the exploitation of this material for possible agricultural purposes (Bindal et al, 2023). Further research is therefore needed to better understand these effects and develop appropriate management strategies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation